Liturgi Kontekstual dalam Perspektif Sacrosanctum Concilium: Refleksi atas Inkulturasi Budaya Dayak di Barito Timur - Marianus Rago Kristeno; Intansakti Pius X (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2026)
Liturgy is the summit and source of life in the Catholic Church. In the celebration of the liturgy, the People of God participate in the mystery of Christ’s death and resurrection. In the context of Indonesia, which consists of diverse ethnicities and cultures, inculturation becomes a highly promising means to make Christ more present in an Indonesian cultural form. This study aims to examine, from theological and pastoral perspectives, the practice of liturgical inculturation in the Catholic Church of East Barito in light of the Second Vatican Council document Sacrosanctum Concilium. The main focus of this research is to understand how Dayak culture is integrated into liturgical celebrations without changing the essence of the Catholic faith and how this process enriches the faith experience of the local community. The research method used is library research, involving an in-depth analysis of Church documents, academic literature, and relevant studies related to contextual liturgy and cultural inculturation. The findings indicate that Sacrosanctum Concilium provides a strong theological foundation for liturgical renewal and openness to local cultural values. Liturgical inculturation in East Barito is manifested through the use of local languages, traditional music, indigenous symbols, and local architecture in the celebration of the liturgy, which deepens the participation of the faithful and strengthens their identity as Dayak Catholics. However, the study also reveals challenges such as the risk of syncretism, superficial understanding of cultural symbols, and differing interpretations between the faithful and Church leaders. Therefore, continuous liturgical formation and intercultural dialogue are necessary so that inculturation does not remain merely aesthetic but truly becomes a means of evangelization and an encounter with Christ who is present within Dayak culture. This research is expected to serve as a reference for developing catechetical and pastoral inculturation in the Indonesian Catholic Church.